(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2012)
A 40-year-old woman having normal menstrual history got admitted into Bangabandhu Sheikh Mujib Medical University (BSMMU) because of vomiting for previous two months, with a background history of irregular steroid intake for her bodyache for about six years. She was gaining weight and gradually losing vision in her right eye and noticed increased body pigmentation. Physical examination revealed BMI 29 kg/m2, generalized pigmentation more marked in palmar crease and oral mucosa, secondary optic atrophy in right eye and papilloedema in left eye. After biochemical and radiological investigation she was diagnosed as a case of Addisons disease with idiopathic intracranial hypertension (IIH) with empty sella DOI: http://dx.doi.org/10.3329/jbcps.v30i1.11368 J Bangladesh Coll Phys Surg 2012; 30: 53-55